La televisión de Loja como herramienta persuasiva en la educación en valores y su incidencia en los adolescentes de la ciudad. Periodo abril- septiembre 2011. Propuesta alternativa - Cumbicus Jaramillo, Angel Francisco (2015)
This research focuses on an analysis of how television lojana constitutes a tool of persuasion on values education and its impact on the youth of the city of Loja, therefore had to make a direct observation in the place where detected the phenomenon, and in this way learn first hand how this media persuades the community especially youth to achieve their purposes. Also, it could determine the level of knowledge among young people who work in this medium, with respect to knowledge about values education and what techniques they use television media to induce cultivation. In this context, it was found that there is ignorance about virtue who have not been trained and do not receive information in this area. Currently, specifically in the city of Loja, which do not contribute to rescue these characteristics of human beings. The results obtained in the field study, to verify depth allowed this problem, because apparently no interest to engage in this task, which would give more vitality to the youth about the importance of human values. The specific objectives were general and verified with the results obtained from the field, where it is estimated that through guidance and education through television, would ensure that the youth of the city of Loja with changing attitudes, behavioral. The results are reflected in the statistical tables with their analysis, both quantitative and qualitative. Similarly, we used several methods that helped them gather as much information that was valid to explain in depth the present investigation. Techniques such as survey and interview were necessary to obtain views and opinions, which should be compared to better understand the problematic situation, and find a solution. Subsequently structured conclusions and recommendations, which highlights the need for precisely the television media to help disseminate information about the cultivation of values among young Loja. KEYWORDS:TV and persuasion, Risk TV, Education, Values, Youth, Media, Alternative.